Tuberculosis prevalence among underfive children in household contact with negative acid fast bacilli adult pulmonary tuberculosis - Harry Iskandar; Heda Melinda D. Nataprawira; Herry Garna; Julistio T.B. Djais (Indonesian Pediatric Society, 2008)
Background Risk of tuberculosis (TB) transmission is greatest if achild has household contact with positive acid fast bacilli (AFB)adult pulmonary TB. Risk of TB transmission from negative AFBadult pulmonary TB to underfive children is unknown.Objective To find out the prevalence of TB infection and diseaseamong underfive children in household contacts with negativeAFB adult pulmonary TB.Methods The study was performed at Balai Kesehatan ParuMasyarakat (BKPM) Bandung on underfive children who live inthe same house with negative AFB adult pulmonary TB fromFebruary to July 2006. History taking, physical examination,anthropometric measurement, chest radiographs, and tuberculinskin test were performed to all study subjects. Subjects were thencategorized as TB infection(positive tuberculin test only) or disease(defined based on Pulmonology Workgroup of IndonesianPaediatrics Council criteria, 2005).Results Sixty one children (32 males and 29 females) had contactwith 54 negative AFB adults pulmonary TB. Tuberculosis infectionwas found in six (10%), while disease was found in 10 (16%)children. The prevalence of TB infection was 10% (95% CI2.3;17.3) while prevalence of TB disease was 16% (95% CI7.1;24.7).Conclusion Tuberculosis infection and disease prevalence isconsiderably high in household contact with negative EFB adultpulmonary TB.